The Practice of the Four Foundations of Mindfulness in Theravada Buddhism within Contemporary Society in Vietnam - Doan, Thanh Phuc; Phramaha Nantakorn Piyabhani; Sanu Mahatthanadull (The Journal of International Buddhist Studies College, 2025)
This study examines the practice of the Four Foundations of Mindfulness (satipaṭṭhāna) in Theravada Buddhism within contemporary Vietnamese society. Three objectives guided the investigation: (1) to identify problematic conditions that impede practice in Vietnam; (2) to analyze canonical articulations of the Four Foundations, with emphasis on the Mahāsatipaṭṭhāna Sutta; and (3) to propose practical, context-sensitive guidelines to support sustainable practice. Qualitative data were collected via focus group discussions and in-depth interviews with practitioners, monastic teachers, and retreat organizers. Data analysis combined SWOT (strengths, weaknesses, opportunities, threats) and thematic content analysis. Results show that mindfulness practices are increasingly adopted for mental and physical well-being but are constrained by inconsistent meditation models, scarcity of experienced mentors, and internal and external distractions, such as unsupportive environments, social obligations, and variable retreat conditions, that undermine insight (vipassanā) development. Canonical analysis corroborates the Mahāsatipaṭṭhāna Sutta’s integrated emphasis on samatha (tranquility) and vipassanā (insight) as mutually reinforcing dimensions of embodied practice applicable to everyday life. Based on these findings, the study proposes tiered retreat models for beginner, intermediate, and advanced practitioners, each structured around three daily sessions (morning, afternoon, evening) and tailored pedagogical content. The OMP model (Organization, Mentor, Participant) is articulated as a pragmatic framework: organizational leadership secures logistics (schedule, accommodation, food, climate), mentors provide guidance and relational support, and participants engage with appropriate discipline and relationality. The study concludes that effective adaptation of the Four Foundations in Vietnam requires coordinated institutional support, mentor development programs, and participant preparation to address identified weaknesses and threats while leveraging local opportunities for culturally rooted, sustainable mindfulness cultivation. Implications include recommendations for standardized retreat curricula, capacity-building for mentors, and institutional partnerships to integrate satipaṭṭhāna practice into community mental health and education. Future research should evaluate the proposed models empirically across diverse Vietnamese contexts to measure outcomes in well-being and conduct.